An Analysis of Main Character’s Gender Dysphoria in Kim Fu’s Novel 'For Today I Am a Boy' (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2020)
This thesis analyzed the transgender process in the main character. The purpose of this thesis is to find out and understand how that happens and to look for the two transgender causes found in the novel. The main character in this novel is a boy who always feels confused with his identity. He always tried to find out who he was, find out which identity he felt comfortable with. But as long as he was confused, he did not get significant support from his family, girlfriends and his friends to stay with the gender he had at that time, instead, they directed him to follow his conscience. All obstacles experienced by the boy in finding his true identity make this novel interesting to look deeper. The theory used to analyze is Theory by Susan Stryker and the concept of diagnostic criteria for gender identity disorder by the American Psychiatric Association. The research method used in this thesis is a qualitative method and library research. The author collected the data from the novel and from several sources of articles, books, and journals related to this thesis. The results of this thesis are to reveal the truth that transgender criteria are truly experienced by the main characters and get the causes of the transgender in his daily lives. Keywords: Dysphoria, Gender identity, Psychology, Transgender